“Collateral damage” of occupation? Social and political responses to nonmarital children of Allied soldiers and Austrian women after the Second World War - Schretter, Lukas; Stelzl-Marx, Barbara (Frontiers in Political Science, 2022)
Thousands of so-called occupation children were born to Allied soldiers and Austrian women in sexual relations after the end of the Second World War. Their experiences correspond to the experiences of occupation children in Germany and, more general, to the experiences of Children Born of War, i.e., children born after sexual contact between local women and foreign/enemy soldiers in conflict and post-conflict situations, regardless of the time of birth and the geopolitical context. Now, more than 75 years after the end of the war, we have studied the changes in the social and political handling of occupation children in Austria over the past decades, using official sources such as newspaper reports, and including biographical interviews conducted with British occupation children in the 2010s. Three phases were identified into which the handling of occupation children can be divided: The post-war years, in which these children were perceived as an (economic) burden; the phase of occupation children growing up and becoming adults, in which they were hardly addressed in public; and the period since the 1990s, in which they have experienced increased media, family, and public interest, which can be attributed to their efforts to make their life stories heard, to the academic research into their living and socialization conditions, and to the formation of networks. The study complements other research on occupation children in Germany and Austria, highlighting the significant differences in the discourse on U.S. American, British, Soviet, and French occupation children, especially between white and Black occupation children, and addressing the differences in Austria compared to Germany. The article argues that challenges and opportunities in the integration of these children have been tied to changes in social values and morals as well as to collective processes of coming to terms with the war and post-war period.